2004
DOI: 10.1074/jbc.m402619200
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Gyrase Recruitment to DNA after UV Light Irradiation in Sulfolobus solfataricus

Abstract: Induction of DNA damage triggers a complex biological response concerning not only repair systems but also virtually every cell function. DNA topoisomerases regulate the level of DNA supercoiling in all DNA transactions. Reverse gyrase is a peculiar DNA topoisomerase, specific to hyperthermophilic microorganisms, which contains a helicase and a topoisomerase IA domain that has the unique ability to introduce positive supercoiling into DNA molecules. We show here that reverse gyrase of the archaean Sulfolobus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 42 publications
(39 reference statements)
3
56
0
Order By: Relevance
“…However, the dose of UV used in that study was high, resulting in fragmentation of nucleic acids. Additionally, it has been observed that the cellular response of Sulfolobus to UV damage involves the recruitment of reverse gyrase to chromatin (32). This combination of DNA damage, cold shock during the 20-min irradiation, and possible topological alterations due to reverse gyrase recruitment may have reduced the levels of Alba bound to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose of UV used in that study was high, resulting in fragmentation of nucleic acids. Additionally, it has been observed that the cellular response of Sulfolobus to UV damage involves the recruitment of reverse gyrase to chromatin (32). This combination of DNA damage, cold shock during the 20-min irradiation, and possible topological alterations due to reverse gyrase recruitment may have reduced the levels of Alba bound to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Eight liters of cell culture were grown at 80°C as described previously (22) until exponential phase (0.4 -0.6 A 600 ). Cells were harvested by centrifugation, and soluble protein extract was prepared as described (17). Soluble extract was incubated for 30 min at 37°C with 20 units/ml Benzonase (Novagen) dialyzed against heparin buffer (20 mM Tris-HCl, pH 7.0) and loaded onto a heparin column (HiPrep 16/10 heparin FF, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…Several results suggest that reverse gyrase might participate in the cell response to DNA damage. In the crenarchaeon Sulfolobus solfataricus, reverse gyrase is recruited to DNA after UV irradiation (17), interacts with the single strand-binding protein (SSB), and the translesion DNA polymerase, PolY (18,19), and is degraded after treatment with methyl methane sulfonate (MMS) (20). Reverse gyrase structure and its involvement in genome stability are reminiscent of the evolutionary conserved complexes comprising topoisomerase III and members of the RecQ helicase family, which have essential functions in recombination and repair (for a recent review, see Ref.…”
mentioning
confidence: 99%
“…Indeed it was shown that a lack of reverse gyrase leads to a significant reduction in the growth rate at a high temperature (13). Several functions related to maintenance of genome integrity have been proposed for reverse gyrase, including a role in rewinding of DNA strands after passage of a transcription complex or during migration of recombination junctions (15,16). Reverse gyrase is able to anneal single-stranded DNA circles, also suggesting an action as a DNA renaturase (14).…”
mentioning
confidence: 99%
“…It was also proposed that reverse gyrase could act as a "resolvase" by removing abnormal DNA structures that impede replication and transcription processes (4). Lastly, it has been shown that reverse gyrase is recruited to DNA in vivo after UV irradiation (15) and that it plays a role in preventing double-stranded DNA breakage at high temperatures (16).…”
mentioning
confidence: 99%